2023
DOI: 10.5194/hess-27-613-2023
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater flow paths drive longitudinal patterns of stream dissolved organic carbon (DOC) concentrations in boreal landscapes

Abstract: Abstract. Preferential groundwater flow paths can influence dissolved organic carbon (DOC) concentration and export in the fluvial network because they facilitate the inflow of terrestrial DOC from large upslope contributing areas to discrete sections of the stream, referred to as discrete riparian inflow points (DRIPs). However, the mechanisms by which DRIPs influence longitudinal patterns of stream DOC concentrations are still poorly understood. In this study, we ask how DRIPs affect longitudinal patterns of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…This is because subsurface water within the riparian zone (P1, Figures 1c and 2, Table ) had DOC concentrations up to an order of magnitude higher than most wetland drains (Figure 2d) and contributed substantial amounts of water to the stream. While little attention has been given to the role of riparian forests as potential sources of DOC to headwater streams in the tropics, studies undertaken at other latitudes have long highlighted riparian forests as hot spots for DOC production and export (e.g., Fiebig et al., 1990; Ledesma et al., 2015; Lupon et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because subsurface water within the riparian zone (P1, Figures 1c and 2, Table ) had DOC concentrations up to an order of magnitude higher than most wetland drains (Figure 2d) and contributed substantial amounts of water to the stream. While little attention has been given to the role of riparian forests as potential sources of DOC to headwater streams in the tropics, studies undertaken at other latitudes have long highlighted riparian forests as hot spots for DOC production and export (e.g., Fiebig et al., 1990; Ledesma et al., 2015; Lupon et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…These areas at the interface between the terrestrial and aquatic ecosystems can exert an important control on stream biogeochemical cycling (Naiman & Décamps, 1997). Research in temperate and boreal regions has shown that discrete points along the riparian corridor can play a significant role in transferring both DOC (Blaurock et al., 2022; Lupon et al., 2023; Ploum et al., 2021) and DIC (Leith et al., 2015; Öquist et al., 2009) to adjacent streams. It is reasonable to expect that these findings from northern regions would also apply to tropical streams.…”
Section: Discussionmentioning
confidence: 99%